THE INFLUENCE OF SELF-CONGRUENCE, CONSUMER, INFLUENCER, AND PRODUCT CONGRUENCE ON IMPULSE BUYING - Natacha, Sharen; Rodhiah, Rodhiah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
A perfect and charming appearance is the desire of everyone. The growing awareness of the importance of self-care has fueled the growth of the beauty industry. Cosmetic companies are thriving, and many local cosmetic brands have begun to emerge. This study aims to analyze the impact of self, consumer, product, and influencer congruence on impulse buying of cosmetic products. The sampling technique used was non-probability sampling, specifically purposive sampling. The sample for this study consisted of 120 female teenagers in Jakarta who have purchased cosmetic products. Data was collected by distributing questionnaires via Google Forms to a sample of regular coffee shop customers in West Jakarta. The data were analyzed using the Structural Equation Modeling (SEM) method with the SmartPLS 4.0 software application. The results of the study showed that Self–Congruence and Influencer–Product Congruence had a positive and significant influence, while Consumer–Influencer Congruence and Consumer–Product Congruence had a positive but insignificant effect. These findings provide valuable insights into how the concept of congruence can affect impulse buying behavior among female teenagers in Jakarta, and these results can be used by local cosmetic companies to enhance their marketing strategies.